Student Entrepreneurship in Digital-Based at Surakarta City - Suci Purwandari; Edy Susena (Indonesian Journal of Banking and Financial Technology, 2023)
Education in Indonesia is growing. Vocational education produces work-ready human resources. Especially in the city of Surakarta many Polytechnics were established, both new permits and changes from academics and high schools. In accordance with the policy of the Ministry of Education, Culture, Research and Technology, Directorate of Vocational Education , on Key Performance Indicators for Graduate Quality that graduates must successfully get a job;/further studies/becoming an entrepreneur. This study used data collection techniques with the Questionnaire method. The questionnaire was distributed to active students at the Polytechnic in Surakarta. The data to be studied are: distribution of entrepreneurship courses, when tostart a business, thebusiness business pursued, marketingmethods, omset obtained per month. Based on research conducted by the author at 5 Polytechnics in Surakarta City with 229 respondents filling in. The number of students who have started a business is 0.04%, students get courses on average in semester 5, students who start a business starting from semester 3, the type of business that occupied the most in the field of services, the most blended marketing methods (with online and offline methods), the turnover obtained on average per month between Rp. 500.000,- – Rp. 1,000,000,-